The manufactures of the United States - Eason, Charles (Statistical and Social Inquiry Society of Ireland, 1884)
The census of the United States is of a much more comprehensive character than that of the United Kingdom. In addition to the collection of facts regarding the people, it includes an inquiry into the wealth of the nation. All the forms of industry are made the subject of inquiry, and the results are embodied in reports upon the quantity and value of all the productions of the country. The statistics of manufactures are contained in a large volume of upwards 1,100 pages, which forms the second volume of the Report of the Tenth Census.
Read before the Society, 29 April 1884
Keywords: U.S. manufactures; American industry; Economic growth; 314.15